Kayu Kacang in KHDTK ULM (Indonesia) is Radermachera quadripinnata (Bignoniaceae), Not Strombosia javanica (Olacaceae) - Muhammad Aldy Nurrachman; Mochamad Arief Soendjoto; Maulana Khalid Riefani (Universitas Pendidikan Mandalika, 2026)
The Special Purpose Forest Area for Education and Training of Lambung Mangkurat University (KHDTK ULM) is a forest area managed by ULM. As an education and training forest, data and information should be obtained in accordance with scientific principles so that they are categorized as valid and accurate. Kayu kacang is a woody plant abundant in this area. The botanical name that is currently consistently used is Strombosia javanica (Olacaceae), even though this name is suspected to be inaccurate. To prove this inaccuracy, this research was conducted in two stages. The first stage was to compare the morphology (physical characteristics) of the leaves, flowers, and fruits of real kayu kacang in the field with that of the kayu kacang botanically named S. javanica. The morphology of the main organs of the latter kayu kacang was obtained from reference searches. If the results were the same, the name could be retained. If not, the name should be changed. The second stage is to obtain an accurate name by comparing the morphological description with a valid identification key. The comparison confirmed that the morphology of the main organs of the real kayu kacang and the reference source was very different. The correct name for the kayu kacang is Radermachera quadripinnata (Bignoniaceae). This botanical name is recommended instead of S. javanica.